CALCULATION OF EFFECTIVE ELECTRODYNAMICAL PARAMETERS FOR COMPOSITES WITH PARTICLES FROM SPECIAL MEDIUMS - V. T. Erofeenko; V. F. Bondarenko (Informatika)
A analytical algorithm for calculation of the effective material parameters of matrix composites consisting of the magnetodielectric matrix and a randomly distributed system of spherical particles is considered. The effective parameters of composites of different types materials such as biisotropical, conducting, nanodimensianal, with lag time and relaxation factor of medium are investigated. Graphical material of computational experiments is presented.